Identification – The Essence of Education - Jeremy Horne (Journal of Systemics, Cybernetics and Informatics)

(untitled)
We use the word "education", often confabulated with "training" when both more accurately fall under the rubric "schooling". Education exists because of training and, conversely, obeying the most fundamental law, the unity of opposites. Yet, an "educated" person is often set apart from the perceived "unwashed masses", their being not so distantly removed from our primate ancestors, dragging their knuckles across the terrain. Trainees are supposed to obey the commands of the educated. Without social context, "education" is a mere word devoid of content. An apparent paradox in the US is the state of its school system, which produces graduates, only half of whom can read past the eighth grade. Our "education" and hubris have managed to bring the much-vaunted Homo sapiens sapiens to the brink of extinction. Effects have caused and impelling our current dilemma is disordered personal identity. The absence of real education is responsible, despite the "sapiens" designation. Schooling exists under the rubric of "formalizing awareness", this is a process as well as an object, resulting in one's becoming, an organic phenomenon. Supervening the hedonistically-characterized path of human development are the mandates of the transcendental realm, represented by the words of Buddha, Christ, Mahoma, Aristotle, and Plato, among others. The "trans" in "transdisciplinary" means "across", with truth (its object and method of seeking it) existing in all domains permeating the Universe and our search for it necessitating our exploring all regions. So, "trans", in this regard, mirrors the "trans" in "transcendental". Truth characterizes the Creator, and so is the object of search in education. Training validates it, evidenced by virtue (internalizing maximal behavior). Truth bespeaks one's identity, its integrity a function of order. A disordered identity compromises a person's being, and conversely. Two methods of identity location are neurocorrelation and deep personal questioning (as with the Voris method). For one with a transcendental ethos, s/he not only lives education; s/he is education.